Socio-medical aspects of oropharyngeal manifestations in the context of the current pandemic - Campeanu , Adriana Teodora; Rus, Mihaela; Petcu, Lucian Cristian; Dumitru, Irina Magdalena (Technium BioChemMed, 2021)
The manifestations occurring at the oropharyngeal level after the onset of the Covid 19 disease represent a current issue in national and international research. This study aims to emphasize the importance of understanding these manifestations and to correlate them with other general chronic diseases, as well as the impact of immunosuppression in the Covid 19 context. The appearance of changes in the sense of taste and smell in the case of patients with Covid is a novelty in viral infections.